Metamorphoses of the concept «revolution» in the context of political and socio-cultural transformations at the turn of the 20th–21st centuries - Sych, O. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract It should be noted that up to the late 20th century there were traced two tendencies concerning the phenomenon of revolution. It goes without saying that the socialist countries were heavily involved in the revolutions and, relevantly, evaluated them as a definitely progressive phenomenon – «engines of history». Simultaneously, the Western countries strongly opposed revolutions; what is more, they conducted special investigations to prevent their occurrence. Since the late 1980’s the situation began to radically change both in the former Soviet Union and the West. Furthermore, this concept has shifted to its positive essence; let’s take the example of «Velvet Revolutions». A series of reforms that began in Eastern Europe after rapid and dramatic events of 1989 were of clearly revolutionary character: the transformation of the political (socialist) system through the introduction of democratic procedures, the establishment of new parties, the spread of pluralism in the ideological and political sphere, the transition to market economy with the full restoration of private property and the like ones. Thus, as a result of the events of 1989 which eliminated pro-Soviet political regimes and held reforms there was a change of social-political and economic order in the countries of Eastern Europe. Therefore, in view of classical definition of the concept of «revolution», these events deserve to be called revolutions or, if ones like, the «velvet revolutions». However, not everything is as straightforward as it seems on the outside. Some scientists believe that in the characteristics of the considered events, the word «revolution» is not chosen very well. Their arguments can be reduced to the following theses. Firstly, none of the Communist government in Eastern Europe was, in fact, overthrown. They all peacefully gave up his powers. At crucial moments, no Communist government did not give the order to shoot at their own citizens who participated in meetings and demonstrations (the exception is Romania, but there is resistance from the side of ruling powers was brief). Gradually in different countries, ruling Communist parties were first forced to compromise with their opponents and then, in most cases, to relinquish part of their power to them. Moreover, the Communist parties reacted loyally to the changing political situation, participated in the first multi-party elections after 1989 and even won them in some countries, though for a while. Secondly, except for Poland, any internal opposition was established, which posed a serious threat to the Communist regime, which had a clear program, in fact, of revolutionary actions, openly declaring their commitment to a radical dismantling of the existing system. Thirdly, the reforms and transformations initiated by the events of 1989 were carried out, as it is unsurprising at first glance, with the participation of a significant and in some countries even the most of recently representatives of the ruling elites. Former representatives of the party-state nomenclature cleverly adapted themselves to the reform process and was able to hold in their hands not only the power (which they had earlier), but also to amass property, as in the socialist period they could not dream of it. However, such a fairly common practice does not correspond to the contents of classic revolution, because the latter just deprives of the pre-revolutionary ruling elite and the ruling classes the power and the ownership. And, fourthly, the revolutions did not lead to the re-establishment of the system, having existed before the previous revolution. In this case, just such a phenomenon is traced: the so-called people’s democratic revolutions in the late 1940’s, having shattered the political and socio-economic order (capitalism), but the Velvet Revolutions restored the essence of these former order though in compliance with the-then parameter. That is why the representatives of the left-wing political views often declare the events of 1989 and, consequently caused social system transformations as counterrevolutions. It would be dubious to categorize so-called «color revolutions» as true ones, since they were applied as specific technologies to oust unwanted leaders or political regimes (including organizing coups) in addition to introducing the Western political and economic model. They are considered to be pseudo-revolutions, which applied only rhetoric, symbols, mass mobilization and other trappings of the revolution, without making any drastic social and economic changes in the society. Regrettably, contemporary political technologists cynically abuse people’s sincere aspirations for freedom and justice, which are closely associated with the concept of «revolution». The well-known American sociologist and political scientist, one of the leading authorities on the study of revolutions, Jack A. Goldstone many years ago wrote: «The belief in revolutions as a symbol of rebirth and liberation remains a powerful political force».